Kebijakan Hukum Pidana Terhadap Pelaku Aborsi Bagi Korban Pemerkosaan di Indonesia - Hazariga, Adam; Hafrida, Hafrida; Siregar, Elizabeth (Universitas Medan Area, 2026)
Abortion resulting from sexual violence remains a controversial moral and legal issue in Indonesia, where women’s bodies are often subject to control by the state, religion, and social morality. The existing legal framework, particularly under Act Number 1 of 2023 on the Criminal Code, continues to reflect a restrictive approach that emphasizes criminalization, while the aspect of post-abortion recovery as part of human rights and reproductive justice has not been adequately accommodated. This study aims to critically examine gender bias, regulatory gaps, and state intervention in determining the 14-week gestational limit for abortion in cases of sexual violence. This research employs a normative juridical method using statutory, conceptual, and comparative approaches. Primary legal materials consist of laws and regulations related to abortion and sexual violence, while secondary materials include relevant scholarly literature, particularly those grounded in Feminist Legal Theory and Reproductive Justice. The analysis is conducted to identify normative inconsistencies, gender bias, and the ideological constructions underlying abortion regulation in Indonesia. The findings reveal that Indonesian law continues to maintain patriarchal assumptions that position the uterus as a moral object rather than as a space of women’s autonomy. Gestational limits, administrative procedures, and restrictive interpretations of legal exceptions tend to exacerbate the burden on victims of sexual violence and create the risk of revictimization. Furthermore, the absence of a comprehensive post-abortion recovery framework reflects inadequate protection of women’s dignity and well-being. This study proposes the concept of Restorative Reproductive Dignity as a legal paradigm that emphasizes the integration of physical, psychological, and social recovery within abortion regulation. This approach advocates a shift from a punitive framework toward a restorative, gender-responsive, and trauma-informed approach aimed at restoring women’s dignity as autonomous legal subjects. Therefore, a reformulation of legal policy aligned with human rights principles is necessary to achieve substantive justice for victims of sexual violence.